Implementation of a reduced complexity algorithm for diversity combining using the universal software radio peripheral - Gacrama, Jonas P.
I have implemented a diversity algorithm that uses real valued weights to reduce the complexity of coherent combining. I have implemented this for the Universal Software Radio Peripheral (USRP). The algorithm starts by selecting the signal with the strongest Signal to Noise Ration (SNR). Then, the other signal branches are vectorially added according to their relative phase from the strongest signal. Real valued weights are used for channel equalization and the sign of the weights ensure that no destructive addition happens during the combining process. Currently, the project lacks on-the-air measurements. Some recommendations are presented to tackle this limitation.